The Anti-Inflammatory Effects of Formononetin, an Active Constituent of Pueraria montana Var. Lobata, via Modulation of Macrophage Autophagy and Polarization - Linyi Xu; Shuo Zhou; Jing Li; Wenbo Yu; Wenyi Gao; Haoming Luo; Xiaoxue Fang (Molecules)
Pueraria montana var. lobata (Willd.) Maesen & S.M.Almeida ex Sanjappa & Predeep (P. lobata) is a medicinal herb widely used in the food and pharmaceutical industries, and studies have shown that P. lobata possesses significant anti-inflammatory pharmacological activities. In this paper, a total of 16 compounds were isolated and identified from P. lobata, among which compounds 1–3, 7, 14, and 16 were isolated from P. lobata for the first time. The results of an in vitro anti-inflammatory activity screening assay showed that compounds 1, 4, 6, 8, and 15 were able to significantly reduce the levels of pro-inflammatory cytokines IL-6 and IL-1β in LPS-induced RAW264.7 macrophages, with the most obvious effect produced by compound 6 (formononetin), while formononetin was able to significantly reduce the number of macrophages at the site of inflammation in transgenic zebrafish. In addition, network pharmacological analysis revealed that the anti-inflammatory activity of formononetin is closely related to autophagy and polarization targets such as TNF, EGFR, PTGS2, and ESR1. In vitro validation experiments showed that formononetin could enhance the expression of LCII/LCI and reduce the expression of P62 protein, reduce the expression of CD86, and enhance the expression of CD206, which further indicated that formononetin could reduce inflammation by regulating macrophage autophagy and polarization processes.